The Role Of Accounting Information Quality In Reducing Information Asymmetry In Damascus Exchange Market - جمعان فادي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aims to study the role of accounting information quality represented by the qualitative characteristics of this information in reducing the asymmetry of information in Damascus Securities Exchange. The researcher has studied the concept of accounting information quality and the factors that affecting it, Information Asymmetry, and Information Asymmetry Measurements. The hypotheses of the research have been tested by preparing a questionnaire and distributing it to a random sample of external auditors practicing the profession in Syrian business environment. the Pearson Correlation Coefficient and multiple linear regression Analysis were used to tests the research hypotheses and reach the results. The research results showed that there is a relationship between the qualitative characteristics of accounting information (Relevance, Credibility, Understandability, Comparability) and the Information Asymmetry in Damascus Securities Exchange. the results also showed that these four characteristics as a whole explain 68.1% of the information asymmetry, which means that there is an important role of accounting information quality in reducing the information asymmetry in Damascus Securities Exchange.